TRADITIONAL USES, PHYTOCHEMISTRY, AND PHARMACOLOGICAL ACTIVITIES OF AMLA WITH SPECIAL REFERENCE OF UNANI MEDICINE - AN UPDATED REVIEW - MASIHUDDIN,; MA, JAFRI; SIDDIQUI, AISHA; CHAUDHARY, SHAHID (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Emblica officinalis, commonly known as Amla belongs to family Euphorbiaceae, is widely used for medicinal purposes in Indian traditional system of medicine (Unani, Ayurveda, and Siddha). It is well known that all parts of Amla are useful in the treatment of various diseases. Various studies on Amla suggest that it has antiviral, antibacterial, and antifungal actions. It is one among those traditional plants, which have a long history of usage as a fruit and remedy. It is amazingly effective as natural antiaging drug. It is a very effectual plant in the treatment of acidity and peptic ulcer. According to Unani literature, it possesses nutritional as well as therapeutic values, and thus, it is one of the herbal nutraceuticals. Modern literature and research studies also prove its medicinal importance. Its fruit is used traditionally as an antioxidant, immunomodulator, antipyretic, analgesic, antitussive, anticancer, and gastroprotective. It is also useful in diarrhea, dysentery, diabetes, fever, headache, mouth ulcer, hair growth, scurvy, and constipation. Phytochemical studies on amla disclosed major chemical constituents including tannins, alkaloids, polyphenol, fatty acid, glycosides, phosphatides, vitamins, and minerals. Gallic acid, ellagic acid, phyllembein, and ascorbic acid are also found to be biologically effective. Various reports show the presence of catechol, β-carotene, flavonoids, pyrogallol, superoxide, and dismutase enzyme in Emblica fruit. In this review, an attempt is made to explore the complete information of E. officinalis including its phytochemistry and pharmacology.